High-transparency low-strength easy-to-tear film and preparation method thereof

By adopting a three-layer structure easy-tear film preparation method and using materials such as high melting index LDPE, HDPE and styrene-butadiene block copolymer, the problems of low transparency and poor easy-tear performance of the existing easy-tear PE film are solved, and the High transparency and good tear-off effect.

CN119348262AActive Publication Date: 2025-01-24QINGDAO DONGHAI PACKAGING IND CO LTD

Patent Information

Application Number
CN202411505892.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-24
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing PE films have low transparency, poor straight-line PE films, and easily cause content to fall when opening the packaging.

Method used

Adopt a three -layer membrane preparation method, the inner layer uses the high -melting finger No. 2 LDPE and No. 1 LDPE, the middle layer is added with HDPE and buty phenyl bun segments, and the outer layer uses high liquidity No. 1 and II LLDPE. By controlling the dosage and composition of each layer, the transparency and tear of the membrane are improved.

Benefits of technology

It achieves high transparency, low haze and good vertical and horizontal tearability, ensuring smooth cuts and less burrs, reducing the risk of contents spilling when the package is opened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119348262A_ABST
    Figure CN119348262A_ABST
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials, and particularly discloses a high-transparency low-strength easy-to-tear film and a preparation method thereof. A high-transparency low-strength easy-to-tear film comprises an inner layer, a middle layer and an outer layer, and the inner layer is prepared from 38-50 parts of LDPE, 50-70 parts of I-type LLDPE, 1.5-2.5 parts of an anti-blocking agent, 2-2.8 parts of a slipping agent, 0.3-0.5 part of an antioxidant and 0.3-0.5 part of a PPA auxiliary agent; the middle layer is prepared from the following raw materials in parts by weight: 25 to 35 parts of No.1 LDPE (Low-Density Polyethylene), 25 to 35 parts of I-1 LLDPE (Linear Low-Density Polyethylene), 8 to 12 parts of HDPE (High-Density Polyethylene), 15 to 25 parts of butylbenzene block copolymer, 0.6 to 1 part of plasticizer, 0.2 to 0.4 part of antioxidant and 8 to 12 parts of filling master batch; and the outer layer is prepared from the following raw materials in parts by weight: 25-35 parts of No.1 LDPE, 60-80 parts of II-type LLDPE, an antioxidant and a plasticizer. The easy-to-tear film has the advantages of being easy to tear in the longitudinal and transverse directions, high in transparency and low in haze.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and more specifically, to a high-transparency, low-strength, easy-tear film and a preparation method thereof. Background Art

[0002] With the development of science and technology and the improvement of living standards, people have put forward various new requirements for packaging materials. People are no longer satisfied with the simple necessary functions of food packaging such as protecting food and extending the shelf life of food, but have put forward higher and higher requirements for the ease of use of food packaging during actual use, especially in the food industry, for example, rice or feed for dogs and cats. A well-known problem with such filling bags is their opening. Often, without using tools (such as knives and scissors), the bag can only be opened with effort at the predetermined sawtooth marks (or small holes or incisions). Another problem is that opening the bag by hand does not produce straight cracks but curved cracks in the bag, increasing the risk of unintentional leakage of the items in the bag. Therefore, there is a need to develop a film for bags that can be easily opened by hand at the incision and produce straight cracks in the bag.

[0003] In the prior art, a Chinese invention patent application document with application number 2019104629104 discloses an easy-to-tear PE film material, a preparation method and an application thereof. The easy-to-tear PE film material has a layered structure, comprising a layer of film composed of the following components by weight: 55-70% polyethylene; 30-40% ethylene cycloolefin copolymer; and 0-5% processing aid.

[0004] The above-mentioned easy-tear PE film material is modified by cyclic olefin copolymer (COC), but it has high haze, low light transmittance and poor transparency, which affects the appearance quality of the product such as shape, color and freshness visually inspected by the senses. It has poor mechanical properties (including low tensile strength and low impact resistance) and general straight-line tearing performance. It needs to be used in combination with other films such as BOPET, aluminum foil and other easy-tear materials to achieve the easy-tear effect by punching tears or serrated lines. However, the tears or serrated lines have poor tearing guidance, which often leads to poor tearing or uneven tear edges, causing the contents to spill. Moreover, the combined use of these materials will still affect the transparency of the easy-tear PE film.

[0005] With respect to the above-mentioned related technologies, the inventors found that the transparency of the current easy-to-tear PE film needs to be improved. Summary of the invention

[0006] In order to simultaneously improve the linear tearability and transparency of the PE film, the present application provides a high-transparency, low-strength tearable film and a preparation method thereof.

[0007] In the first aspect, the present application provides a highly transparent, low-strength, easy-to-tear film, which adopts the following technical solution: A highly transparent, low-strength, easy-to-tear film, comprising an inner layer, a middle layer and an outer layer, wherein the inner layer comprises the following raw materials in parts by weight: 38-50 parts of LDPE, 50-70 parts of Class I LLDPE, 1.5-2.5 parts of an anti-blocking agent, 2-2.8 parts of a slip agent, 0.3-0.5 parts of an antioxidant, and 0.3-0.5 parts of a PPA additive; The LDPE in the inner layer includes No. 1 LDPE and No. 2 LDPE in a mass ratio of 10:1-1.5, the melt index of No. 1 LDPE is 1.9-2 g / 10 min, and the density is 0.924-0.925 g / cm 3 The melt index of LDPE No. 2 is 4-5g / 10min and the density is 0.923-0.925g / cm 3 ; The type I LLDPE in the inner layer includes type I-1 LLDPE and type I-2 LLDPE in a mass ratio of 1.5-2:1, the melt index of type I-1 LLDPE is 2 g / 10 min, and the density is 0.918-0.92 g / cm 3 , the melt index of LLDPE No. 1-2 is 4-10g / 10min; The middle layer comprises the following raw materials in parts by weight: 25-35 parts of No. 1 LDPE, 25-35 parts of No. 1-1 LLDPE, 8-12 parts of HDPE, 15-25 parts of butadiene-styrene block copolymer, 0.6-1 parts of plasticizer, 0.2-0.4 parts of antioxidant, and 8-12 parts of filler masterbatch; The outer layer comprises the following raw materials in parts by weight: 25-35 parts of No. 1 LDPE, 60-80 parts of Class II LLDPE, 0.3-0.5 parts of antioxidant, and 0.6-1 parts of plasticizer.

[0008] By adopting the above technical scheme, high melt index No. 2 LDPE is used in the inner layer, which has high transparency, excellent processability and ductility. In addition, when used in combination with No. 1 LDPE, the plastic film can not only have good longitudinal and transverse straight-line tearing effect, but also have good transparency. At the same time, Class I LLDPE is added, in which two types of LLDPE with melt index are used, which can be evenly dispersed in the inner layer, which not only enhances the straight-line tearing effect, but also has good low-temperature heat sealing properties. The opening agent can reduce the surface friction coefficient of the film, so that the easy-tear film has good opening performance. The slip agent can reduce the surface friction coefficient, so that the easy-tear film can be smoother.

[0009] No. 1 LDPE and No. I-1 LLDPE are used in the middle layer. No. I-1 LLDPE has a high melt index and is suitable for cast production. It has excellent dimensional stability, impact resistance and stiffness. After the two resins are mixed, a film with good stiffness and transparency can be obtained, which further improves the tearability. In addition, butadiene block copolymer is added to the middle layer, which has high rigidity, good heat sealing properties, high gloss and clarity, good toughness, and can improve the transparency and tearability of the film.

[0010] No. 1 LDPE and another LLDPE are used in the outer layer. No. 1 LDPE has high fluidity and better processing performance, is suitable for cast film production, and has high gloss and transparency after casting, low haze, high impact resistance, and is easy to tear in the longitudinal and transverse directions.

[0011] The film made of the above materials has higher transparency and lower haze, and is easier to tear in the vertical and horizontal directions. When hot cutting, it is not easy to produce the phenomenon of uncut or burrs on the edge of the cut and uneven knots.

[0012] Optionally, the type II LLDPE in the outer layer includes type II-1 LLDPE and type II-2 LLDPE in a mass ratio of 2:4-5, and the density of type II-1 LLDPE is 0.924-0.925 g / cm 3 , the melt index is 20g / 10min, and the density of II-2 LLDPE is 0.915-0.921g / cm 3 , the melt index is 1.6-2.4g / 10min.

[0013] By adopting the above technical solution, the outer layer adopts II-1 LLDPE with a higher melt index (ExxonMobil, brand 6101XR, melt index of 20g / 10min, density of 0.924g / cm 3 ), it has good fluidity, excellent thermal stability and stiffness, strong resistance to environmental stress cracking, and can effectively improve the transverse and longitudinal tearing effects of the easy-tear film. II-2 LLDPE also has good melt fluidity, and has high tensile, penetration and impact resistance.

[0014] Optionally, the density of HDPE in the outer layer is 0.95-0.9554 g / cm 3 , the melt index is 0.17-0.2g / 10min.

[0015] By adopting the above technical solution, the HDPE with the density and melt index has higher strength and hardness, which can improve the stiffness of the easy-tear film and reduce the cost at the same time.

[0016] Optionally, the density of the styrene-butadiene block copolymer is 1.01 g / cm 3, the melt index is 7.5g / 10min.

[0017] By adopting the above technical scheme, at a certain temperature, the thermal motion of the styrene-butadiene block copolymer and various polyethylene molecules in the middle layer is increased, thereby promoting mutual solubility, allowing the styrene-butadiene block copolymer to be dispersed in the polymer to form a uniform two-phase structure, destroying the original interaction between the polyethylene molecules, allowing the molecules to be reoriented and arranged, and improving the tearability of the polyethylene film.

[0018] Optionally, the filler masterbatch comprises the following raw materials in parts by weight: 0.3-0.4 parts of filler, 4-5 parts of HDPE, 0.03-0.04 parts of bisaminosilane coupling agent, 1-1.5 parts of EVOH, and 0.15-0.2 parts of maleic anhydride grafted HDPE.

[0019] By adopting the above technical scheme, the filling masterbatch is arranged in the middle layer, and the filling masterbatch is made of raw materials such as HDPE and bisaminosilane coupling agent. EVOH is a copolymer of ethylene and vinyl acetate. Its interaction with polyethylene may lead to the restriction of the movement of polyethylene molecular chains, hinder the crystallization of PE, and reduce its crystallization rate. Maleic anhydride is used to graft HDPE as a compatibilizer, which can form a chemical reaction with EVOH. This compatibility may make heterogeneous nucleation more obvious, affect the normal crystallization of polyethylene, slow down its grain growth rate, and to a certain extent refine the grains, blur the interface between crystals, make the light beam easier to pass through, and reduce the haze. The bisaminosilane coupling agent can improve the compatibility of the filler with HDPE and EVOH. The filling masterbatch makes the heterogeneous nucleation effect of polyethylene gradually significant during the crystallization process, further increases the density of the crystal nucleus, improves the dispersion of the crystal nucleus, and significantly refines the grains inside the material, reduces the spherulites, and reduces the light reflection and light scattering on the surface of the film, thereby reducing the haze of the film and increasing the transparency.

[0020] Optionally, the preparation method of the filling masterbatch is as follows: The filler and the bisaminosilane coupling agent are mixed, and stirred at 60-70° C. and 5000-6000 rpm for 20-30 minutes to prepare a pretreated filler; The pretreated filler is mixed with HDPE, EVOH and maleic anhydride grafted HDPE, melted and extruded to form pellets.

[0021] By adopting the above technical scheme, the filler is firstly surface-modified with a bisaminosilane coupling agent, thereby increasing its compatibility with EVOH and HDPE and improving its dispersion uniformity, and then a filler masterbatch is obtained through blending and granulation.

[0022] Optionally, the filler is selected from at least one of barium sulfate, calcium carbonate, silicon dioxide and talc.

[0023] By adopting the above technical scheme, barium sulfate has high transparency and has little effect on the transparency of the plastic film, thereby obtaining an easy-to-tear film with high gloss and transparency. Calcium carbonate can reduce costs, increase production efficiency, reduce deformation caused by tearing, and obtain a better straight-line easy-to-tear effect. Talc can improve dimensional stability and surface scratch resistance, enhance dimensional stability, and improve product quality. Silica can increase weather resistance, improve melt fluidity, and improve thermal stability, making it easier to tear.

[0024] Optionally, the thickness ratio of the inner layer, the middle layer and the outer layer is 1:2-3:1-2.

[0025] By adopting the above technical solution, the thickness of the middle layer and the outer layer is relatively high, which can increase the hot air performance of the easy-tear film, ensure its easy-tear effect, and improve the barrier performance of the film.

[0026] Optionally, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 168, antioxidant 1076 and antioxidant 1098; The plasticizer is selected from at least one of dioctyl phthalate, dibutyl phthalate, epoxidized soybean oil and epoxy fatty acid butyl ester.

[0027] By adopting the above technical solution, the oxidant can prevent the plastic film from being degraded and oxidized due to the passage of factors such as heat, light and oxygen during processing, storage and use, avoid the plastic film from changing in color and performance due to oxidation, and maintain the original performance and appearance.

[0028] Plasticizers can increase the fluidity of various polyethylene molecules, lower the glass transition temperature, and improve the flexibility, elongation, plasticity and processability of polyethylene.

[0029] In a second aspect, the present application provides a method for preparing a high-transparency, low-strength, easy-to-tear film, using the following technical solution: A method for preparing a high-transparency, low-strength, easy-to-tear film comprises the following steps: Ingredients: The raw materials of the inner layer, the middle layer and the outer layer are mixed evenly to obtain the inner layer material, the middle layer material and the outer layer material; Heating: Heat the outer layer main machine to 195-230℃, the middle layer main machine to 195-230℃, the inner layer main machine to 195-230℃, and the die head temperature is 195-205℃; Blow molding: Place the inner layer material, middle layer material and outer layer material into the corresponding main machine respectively, and obtain film bubbles through hot melting, casting, film drawing, blowing and pulling; Rewinding: After corona treatment, the film bubble is cut, rolled and packaged.

[0030] By adopting the above technical solution, the temperature of each layer of the main machine is controlled at 195-230℃. By accurately controlling the temperature stability of each zone, the plasticization of LDPE resin is maximized to prevent high temperature from causing resin decomposition, and to prevent low temperature from causing poor resin plasticization, resulting in reduced surface gloss and transparency of the PE film, thereby improving processing performance.

[0031] In summary, this application has the following beneficial effects: 1. Since the present application adopts a specific amount of LDPE (including No. 1 LDPE and No. 2 LDPE) and LLDPE (including No. I-1 LLDPE and No. I-2 LLDPE), and the melt index of No. 2 LDPE and No. I-2 LLDPE is relatively high, HDPE and filler masterbatch are used in the middle layer, and No. 1 LDPE and Class II LLDPE are used in the outer layer. The easy-tear film obtained thereby has lower haze, stronger transparency and glossiness, and good longitudinal and transverse tearability, a smooth incision, and is not prone to burrs.

[0032] 2. In the present application, fillers and bisaminosilane coupling agents, HDPE, EVOH and maleic anhydride grafted HDPE are preferably used to prepare filler masterbatch, which can effectively reduce the grain refinement of polyethylene, reduce haze and improve transparency.

[0033] 3. The method of the present application improves the longitudinal and transverse tensile strength by controlling the processing temperature of the extruder, thereby maintaining good stiffness and tearability while increasing transparency and reducing haze. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of the linear tear test method for high-transparency, low-strength, easy-tear films. DETAILED DESCRIPTION

[0035] The following examples further illustrate the present application in detail.

[0036] Preparation Example 1-4 of Filling Masterbatch The density of HDPE in the preparation example is 0.9554 g / cm 3 The melt index (190°C, 2.16kg) is 0.17g / 10min. It is selected from Zhenhai Refining and Chemical, model ZH5502H. The bisaminosilane coupling agent is selected from Dow Corning OFS-6020. The EVOH is selected from Japan Kuraray, model H171B. The maleic anhydride grafted HDPE is selected from France Arkema, model 18410P.

[0037] Preparation Example 1: 0.4 kg of filler and 0.04 kg of bisaminosilane coupling agent were mixed, and stirred at 60° C. and 5000 rpm for 30 min to prepare a pretreated filler, wherein the filler was barium sulfate; The pretreated filler was mixed with 4 kg HDPE, 1 kg EVOH and 0.15 kg maleic anhydride grafted HDPE, heated to 200° C., extruded at a rotation speed of 50 rpm, and pelletized.

[0038] Preparation Example 2: 0.3 kg of filler and 0.03 kg of bisaminosilane coupling agent were mixed, and stirred at 70° C. and 6000 rpm for 20 min to prepare a pretreated filler, wherein the filler was barium sulfate; The pretreated filler was mixed with 5 kg HDPE, 1.5 kg EVOH and 0.2 kg maleic anhydride grafted HDPE, heated to 200° C., extruded at a rotation speed of 50 rpm, and pelletized.

[0039] Preparation Example 3: The difference from Preparation Example 1 is that an equal amount of HDPE is used to replace EVOH.

[0040] Preparation Example 4: The difference from Preparation Example 1 is that an equal amount of HDPE is used to replace the maleic anhydride grafted HDPE. Example

[0041] The sources of the raw materials in the following examples are shown in Table 1.

[0042] Table 1 Sources of raw materials in high-transparency, low-strength, easy-tear films Example 1: A highly transparent, low-strength, tearable film, comprising an inner layer, an intermediate layer and an outer layer connected to each other, wherein the thickness ratio of the inner layer, the intermediate layer and the outer layer is 1:3:1, and the amount of raw materials used in each layer is as shown in Table 2. The LDPE in the inner layer comprises No. 1 LDPE and No. 2 LDPE in a mass ratio of 10:1, and the density of No. 1 LDPE is 0.924 g / cm 3 , the melt index (190℃, 2.16kg) is 1.9g / 10min, and the density of LDPE No. 2 is 0.923g / cm 3 , the melt index (190℃, 2.16kg) is 4g / 10min; Class I LLDPE includes I-1 LLDPE and I-2 LLDPE with a mass ratio of 2:1, and the density of I-1 LLDPE is 0.918g / cm 3 The melt index (190℃, 2.16kg) is 2g / 10min, the melt index of I-2 LLDPE is 4g / 10min; the melt index (190℃, 2.16kg) of HDPE in the middle layer is 0.17g / 10min, and the density is 0.9554g / cm 3 The melt index (200°C, 5kg) of the butadiene-styrene block copolymer is 7.5g / 10min and the density is 1.01g / cm3 ; The type II LLDPE in the outer layer includes type II-1 LLDPE and type II-2 LLDPE in a mass ratio of 2:5. The density of type II-1 LLDPE is 0.924 g / cm 3 , the melt index is 20g / 10min, and the density of II-2 LLDPE is 0.918g / cm 3 , melt index is 1.9g / 10min; The antioxidants in the inner layer, the middle layer and the outer layer are all antioxidant 1010, the plasticizers in the middle layer and the outer layer are all epoxidized soybean oil, and the filling masterbatch in the middle layer is selected from Dongguan Changping Sanlong Plastic Products, model T60.

[0043] The method for preparing the above-mentioned high-transparency, low-strength, easy-tear film comprises the following steps: S1. Ingredients: According to the amount of raw materials for each layer in Table 2, weigh the raw materials and mix them evenly to obtain inner layer materials, middle layer materials and outer layer materials; S2. Heating: The film blowing unit is heated up continuously in different zones. The temperatures of each zone of the die head are: 195℃ for zone 1, 200℃ for zone 2, 205℃ for zone 3 and 205℃ for zone 4. The temperatures of each zone of the outer layer host are: 195℃ for zone 1, 220℃ for zone 2, 225℃ for zone 3, 230℃ for zone 4, 230℃ for zone 5 and 225℃ for zone 6. The temperatures of each layer of the middle layer host are: 195℃ for zone 1, 220℃ for zone 2, 225℃ for zone 3, 230℃ for zone 4, 230℃ for zone 5 and 225℃ for zone 6. The temperatures of each zone of the inner layer host are: 195℃ for zone 1, 220℃ for zone 2, 225℃ for zone 3, 230℃ for zone 4, 230℃ for zone 5 and 225℃ for zone 6. After heating up, keep warm for 20 minutes and start the machines in the order of outer layer, middle layer and inner layer. The time interval between starting the machines is 2 minutes. S3, blow molding: place the inner layer material, the middle layer material and the outer layer material into the corresponding main machine respectively, the outer layer main machine speed is 50r / min, the middle layer main machine speed is 150r / min, the inner layer main machine speed is 50min, the air inlet temperature is 20℃, after hot melting, pull upward and quickly knead the molten glue, rush compressed air into the die head, the blowing ratio is 3, pull up the film bubble at a uniform speed, the pulling speed is 19m / min, and the pulling ratio is 6; S4, winding: corona treatment is performed on the film bubble to make the surface tension of the film 40mN / m, and the film is cut into two pieces, wound and packaged.

[0044] Table 2 Raw material dosage of high transparency low strength easy-tear film in Examples 1-8 Example 2-3: A highly transparent, low-strength, easily tearable film. The difference from Example 1 is that the amount of raw materials used in each layer is as shown in Table 2.

[0045] Example 4: A highly transparent, low-strength, easily tearable film, which differs from Example 1 in that the mass ratio of LLDPE No. II-1 to LLDPE No. II-2 in the outer layer is 2:4.

[0046] Example 5: A highly transparent, low-strength, easily tearable film. The difference from Example 1 is that LLDPE No. II-2 is used in the outer layer instead of LLDPE No. II-1.

[0047] Example 6: A highly transparent, low-strength, easily tearable film. The difference from Example 1 is that LLDPE No. II-1 is used in the outer layer instead of LLDPE No. II-2.

[0048] Example 7: A highly transparent, low-strength, easily tearable film, which differs from Example 1 in that the mass ratio of LLDPE No. II-1 to LLDPE No. II-2 in the outer layer is 1:6.

[0049] Example 8: A highly transparent, low-strength, easily tearable film, which differs from Example 1 in that the mass ratio of LLDPE No. II-1 to LLDPE No. II-2 in the outer layer is 3:4.

[0050] Example 9: A highly transparent, low-strength, easy-to-tear film. The difference from Example 1 is that the styrene-butadiene block copolymer is selected from Swiss Ineos Styrolux, model number is Styrolux693D, and density is 1.01 g / cm 3 , melt index (200℃, 5kg) is 12.5cm 3 / 10min Example 10: A highly transparent, low-strength, easily tearable film, which differs from Example 1 in that the masterbatch filled in the middle layer is made from Preparation Example 1.

[0051] Example 11: A high-transparency, low-strength, easy-tear film, which is different from Example 1 in that the filling masterbatch is made from Preparation Example 2.

[0052] Example 12: A high-transparency, low-strength, easy-tear film, which is different from Example 10 in that the filling masterbatch is made from Preparation Example 3.

[0053] Example 13: A high-transparency, low-strength, easy-tear film, which is different from Example 10 in that the filling masterbatch is made from Preparation Example 4.

[0054] Comparative Example Comparative Examples 1-8: A highly transparent, low-strength, easily tearable film, the amounts of raw materials used are shown in Table 3. Compared with Example 1, in the inner layer of Comparative Example 1, an equal amount of No. 1 LDPE is used to replace No. 2 LDPE, the mass ratio of No. 1 LDPE to No. 2 LDPE in the inner layer of Comparative Example 2 is 7:1, the mass ratio of No. 1 LDPE to No. 2 LDPE in the inner layer of Comparative Example 3 is 12:1, and in the inner layer of Comparative Example 4, an equal amount of No. 1-1 LDPE is used to replace No. 1-2 LLDPE, the mass ratio of No. 1-1 LDPE to No. 1-2 LLDPE in the inner layer of Comparative Example 5 is 1:1, the mass ratio of No. 1-1 LDPE to No. 1-2 LLDPE in the inner layer of Comparative Example 6 is 3:1, the amount of HDPE in the middle layer of Comparative Example 7 is doubled, and no butadiene block copolymer is added to the middle layer of Comparative Example 8.

[0055] Table 3 Raw material dosage of high transparent low strength easy-tear film in comparative examples 1-8 Performance Test A high-transparency, low-strength, easy-tear film with a thickness of 20 μm was prepared according to the raw materials and methods in the examples and comparative examples, and the performance test was carried out according to the following method. The test results are recorded in Table 4.

[0056] 1. Tensile strength at break and elongation at break: Tested in accordance with GB / T13022-1991 "Test method for tensile properties of plastic films".

[0057] 2. Tear strength: Test in accordance with GB / T16578-1996 "Test method for tear resistance of plastic films and sheets".

[0058] 3. Light transmittance and haze: Test in accordance with GB / T2410-2008 "Test method for light transmittance and haze of transparent plastics"; 4. Linear tearing performance: Cut the film into a rectangle with a width (W1) of 4 cm and a length of 20 cm, cut a slit in the middle of the width, tear it along a straight line, and then measure the width of the other end (W2) of the sample. Figure 1 The tearing deviation α is calculated by the following formula. The lower the α value, the better the linear tearing performance of the film. α=[(1 / 2W1)-W2] / (1 / 2W1)×100%.

[0059] Table 4 Performance test results of high-transparency, low-strength, easy-tear films It can be seen from the data in Table 1 that in Examples 1-4, LDPE No. 1 and LDPE No. 2 are used in a mass ratio of 10:1, LLDPE No. I-1 and LLDPE No. I-2 are used in a mass ratio of 2:1, and low-addition HDPE is used in the middle layer, and LLDPE No. II-1 and LLDPE No. II-2 are used in a mass ratio of 2:5 in the outer layer. The easy-tear film thus prepared has a light transmittance of more than 93%, a haze of less than 5%, and a tear deviation of less than 7%, and has good linear tearing performance. In addition, the test values ​​of tensile strength at break, elongation at break, and tear strength are low, and have a good easy-tear effect.

[0060] Compared with Example 1, Comparative Example 5 does not add LLDPE No. II-1 in the outer layer, and uses LLDPE No. II-2 to replace LLDPE No. II-1. Example 6 uses LLDPE No. II-1 to replace LLDPE No. II-2 in the outer layer. The melt index of LLDPE No. II-1 is 20 g / 10 min, while the melt index of LLDPE No. II-2 is 1.9 g / 10 min. It can be seen from the data in Table 4 that the tensile strength at break, elongation at break, and tear strength of the easy-tear films prepared in Examples 5 and 6 are increased, and the light transmittance is reduced, the haze is increased, the tear deviation is increased, and the linear tearing effect is deteriorated.

[0061] Compared with Example 1, the usage ratios of LLDPE No. II-1 and LLDPE No. II-2 in Example 7 and Example 8 are 1:6 and 3:4 respectively. Table 4 shows that the mechanical properties of the easy-tear films prepared in Example 7 and Example 8 are increased, the easy-tear effect is reduced, and the transparency is weakened.

[0062] In Example 9, a styrene-butadiene block copolymer with an increased melt index is used. It can be seen that the transparency of the easy-tear film prepared therefrom is reduced, and the easy-tear effect is weakened.

[0063] Compared with Example 1, Example 10 and Example 11 respectively use the filling masterbatch prepared in Preparation Example 1 and Preparation Example 2. The data in Table 4 show that the elongation at break, tensile strength at break and tear strength test results of the easy-tear films prepared in Example 10 and Example 11 are all increased, and the light transmittance is increased, the transparency is improved, the tear deviation is reduced, and the straight-line easy-tear effect is increased.

[0064] In Example 12, the filling masterbatch prepared in Preparation Example 3 was used. Compared with Example 10, HDPE was used instead of EVOH in the filling masterbatch in Preparation Example 3. In Example 13, the filling masterbatch prepared in Preparation Example 4 was used. Compared with Example 10, an equal amount of HDPE was used in Preparation Example 4 to replace maleic anhydride grafted HDPE. It can be seen from the data in Table 4 that the mechanical strength of the easy-tear films prepared in Examples 12 and 13 is increased, the easy-tear effect is deteriorated, and the linear tearing performance is weakened.

[0065] Compared with Example 1, Comparative Example 1 uses No. 1 HDPE to replace No. 2 LDPE in the inner layer. It can be seen that the mechanical strength of the easy-tear film prepared in Comparative Example 1 is increased, the easy-tear effect is weakened, the transparency is also reduced, and the linear tearing effect is worse.

[0066] Compared with Example 1, the mass ratios of LDPE No. 1 and LDPE No. 2 in Comparative Examples 2 and 3 are 7:1 and 13:1 respectively. The mechanical strengths of the easy-tear films made in Comparative Examples 2 and 3 are increased compared with Example 1, but are improved compared with Comparative Example 1.

[0067] In Comparative Example 4, an equal amount of LDPE No. 1-1 is used to replace LLDPE No. 1-2. The mass ratios of LDPE No. 1-1 and LLDPE No. 1-2 in Comparative Examples 5 and 6 are 1:1 and 3:1, respectively. It can be seen that compared with Example 1, the mechanical strength of the easy-tear films prepared in Comparative Examples 4-6 is increased, while the increase in Comparative Examples 5 and 6 is less than that in Comparative Example 4, indicating that the usage ratio of LDPE No. 1-1 and LLDPE No. 1-2 has a greater influence on the easy-tear effect of the film.

[0068] Compared with Example 1, Comparative Example 7 increases the amount of HDPE in the middle layer. Compared with Example 1, Comparative Example 8 does not add butadiene block copolymer in the middle layer. The mechanical strength of the easy-tear films prepared in Comparative Examples 7 and 8 is increased, the linear tearing performance is reduced, and the transparency is also reduced.

[0069] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A highly transparent, low-strength, easy-to-tear film, characterized in that: It comprises an inner layer, a middle layer and an outer layer, wherein the inner layer comprises the following raw materials in parts by weight: 38-50 parts of LDPE, 50-70 parts of Class I LLDPE, 1.5-2.5 parts of an anti-blocking agent, 2-2.8 parts of a lubricant, 0.3-0.5 parts of an antioxidant, and 0.3-0.5 parts of a PPA additive; The LDPE in the inner layer includes No. 1 LDPE and No. 2 LDPE in a mass ratio of 10:1-1.5, the melt index of No. 1 LDPE is 1.9-2 g / 10 min, and the density is 0.924-0.925 g / cm 3 The melt index of LDPE No. 2 is 4-5g / 10min and the density is 0.923-0.925g / cm 3 ; The type I LLDPE in the inner layer includes type I-1 LLDPE and type I-2 LLDPE in a mass ratio of 1.5-2:1, the melt index of type I-1 LLDPE is 2 g / 10 min, and the density is 0.918-0.92 g / cm 3 , the melt index of LLDPE No. 1-2 is 4-10g / 10min; The middle layer comprises the following raw materials in parts by weight: 25-35 parts of No. 1 LDPE, 25-35 parts of No. 1-1 LLDPE, 8-12 parts of HDPE, 15-25 parts of butadiene-styrene block copolymer, 0.6-1 parts of plasticizer, 0.2-0.4 parts of antioxidant, and 8-12 parts of filler masterbatch; The outer layer comprises the following raw materials in parts by weight: 25-35 parts of No. 1 LDPE, 60-80 parts of Class II LLDPE, 0.3-0.5 parts of antioxidant, and 0.6-1 parts of plasticizer.

2. The high-transparency, low-strength, easy-tear film according to claim 1, characterized in that: The type II LLDPE in the outer layer includes type II-1 LLDPE and type II-2 LLDPE in a mass ratio of 2:4-5, and the density of type II-1 LLDPE is 0.924-0.925 g / cm 3 , the melt index is 20g / 10min, and the density of II-2 LLDPE is 0.915-0.921g / cm 3 , the melt index is 1.6-2.4g / 10min.

3. The high-transparency, low-strength, easy-tear film according to claim 1, characterized in that: The density of HDPE in the outer layer is 0.95-0.9554 g / cm 3 , the melt index is 0.17-0.2g / 10min.

4. The high-transparency, low-strength, easy-tear film according to claim 1, characterized in that: The density of the styrene-butadiene block copolymer is 1.01 g / cm 3 , the melt index is 7.5g / 10min.

5. The high-transparency, low-strength, easy-tear film according to claim 1, characterized in that: The filler masterbatch comprises the following raw materials in parts by weight: 0.3-0.4 parts of filler, 4-5 parts of HDPE, 0.03-0.04 parts of bisaminosilane coupling agent, 1-1.5 parts of EVOH, and 0.15-0.2 parts of maleic anhydride grafted HDPE.

6. The high-transparency, low-strength, easy-tear film according to claim 5, characterized in that: The preparation method of the filling masterbatch is as follows: The filler and the bisaminosilane coupling agent are mixed, and stirred at 60-70° C. and 5000-6000 rpm for 20-30 minutes to prepare a pretreated filler; The pretreated filler is mixed with HDPE, EVOH and maleic anhydride grafted HDPE, melted and extruded to form pellets.

7. The high-transparency, low-strength, easy-tear film according to claim 5, characterized in that: The filler is selected from at least one of barium sulfate, calcium carbonate, silicon dioxide and talc.

8. The high-transparency, low-strength, easy-tear film according to claim 1, characterized in that: The thickness ratio of the inner layer, the middle layer and the outer layer is 1:2-3:1-2.

9. The high-transparency, low-strength, easy-tear film according to claim 1, characterized in that: The antioxidant is selected from at least one of antioxidant 1010, antioxidant 168, antioxidant 1076 and antioxidant 1098; The plasticizer is selected from at least one of dioctyl phthalate, dibutyl phthalate, epoxidized soybean oil and epoxy fatty acid butyl ester.

10. The method for preparing the high-transparency, low-strength, easy-tear film according to any one of claims 1 to 9, characterized in that: The following steps are involved: Ingredients: The raw materials of the inner layer, the middle layer and the outer layer are mixed evenly to obtain the inner layer material, the middle layer material and the outer layer material; Heating: Heat the outer layer main machine to 195-230℃, the middle layer main machine to 195-230℃, the inner layer main machine to 195-230℃, and the die head temperature is 195-205℃; Blow molding: Place the inner layer material, middle layer material and outer layer material into the corresponding main machine respectively, and obtain film bubbles through hot melting, casting, film drawing, blowing and pulling; Rewinding: After corona treatment, the film bubble is cut, rolled and packaged.

Citation Information

Patent Citations

  • Ultra-low-strength easy-to-tear PE film and preparation process thereof

    CN114030258A

  • High-transparency polyethylene heat shrink film and preparation method thereof

    CN116728930A

  • Easily tearable multilayer film and packaging material

    JP2015160374A

  • Anti-sticking master batch for BOPE film, preparation method therefor, and use thereof

    WO2024037440A1

  • AU2013206643A1

Cited By

  • Linear easy-to-tear film and preparation method thereof

    CN119795719A

  • Transverse linear easy-to-tear PE film and preparation method thereof

    CN120171140A

  • Rail train gravity energy storage system

    CN121162481A